The effect of increased levels of reactive oxygen species in ejaculate on parameters of reproductive function in men with low fertility - Feskov, O.M.; Zhylkova, Ye.; Feskova, I.A.; Ivanova, G.V.; Blazhko, O.V. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2024)
A high level of reactive oxygen species (ROS) in the ejaculate is one of the reasons for the failure in male reproductive function. Oxidative stress is defined as an imbalance between the formation of reactive oxygen species and the ability of the antioxidant system to detoxify them. An excess of reactive oxygen species in sperm can initiate pathological changes in spermatozoa, causing oxidative damage to cell membranes, proteins and DNA. Measurement of the content of reactive oxygen species is hindered by the lack of standardization. This study determined the effect of oxidative stress on standard microscopic parameters of the spermogram and the DNA fragmentation level of spermatozoa in the ejaculate of men with reduced reproductive function. The obtained results confirm the significant role of the detoxification system in maintaining normal microscopic parameters of the spermogram. A negative effect of a high level of reactive oxygen species in the ejaculate on the sperm motility, concentration and morphology of spermatozoa in men with reduced fertility was established (p<0.05). It is shown that the level of oxidative stress in the ejaculate is statistically significantly higher in patients with reduced parameters of the spermogram, compared with this indicator for men with normal indicators of reproductive function (p<0.01). No influence of men's age on microscopic indicators of ejaculate was  found. No correlation was  established between the level of reactive oxygen species and the percentage of spermatozoa with fragmented DNA in the ejaculate. However, it was shown that the proportion of spermatozoa with fragmented DNA is significantly higher in infertile patients compared to the group of men with normal reproductive function (p<0.05). Therefore, a high level of sperm DNA fragmentation in the ejaculate can also be considered as  one of the reasons for the decline in male fertility. The necessity of determining the level of oxidative stress in men with reduced spermogram parameters as part of an examination to find out the causes of infertility in a couple has been proven. In the future, it is necessary to standardize the rules for taking the material and performing the analysis for determining the level of reactive oxygen species in the ejaculate.